2014
DOI: 10.1186/1471-2261-14-72
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade and para-aortic hematoma post elective surgical myocardial revascularization on a beating heart – a possible complication of the Lima-stitch and sequential venous anastomosis

Abstract: BackgroundOff-pump coronary artery bypass (OPCAB) surgery can be associated with some intrinsic, but relatively rare complications. A pericardial effusion is a common finding after cardiac surgeries, but the prevalence of a cardiac tamponade does not exceed 2% and is less frequent after myocardial revascularization.Authors believe that in our patient an injury of a nutritional pericardial or descending aorta vessel caused by the Lima stitch resulted in oozing bleeding, which gradually leaded to cardiac tampona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The area surrounding the LLPV immediately behind the pericardium in case 1 and the wide area along with the diaphragm in case 2 are notable examples for the localization of the injury site. The previous reports identified the aorta, pulmonary veins, esophagus, and lung as organs susceptible to injuries by DPS [3][4][5][6]. Our case 2 suggested that the diaphragm also requires attention during DPS stitching.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The area surrounding the LLPV immediately behind the pericardium in case 1 and the wide area along with the diaphragm in case 2 are notable examples for the localization of the injury site. The previous reports identified the aorta, pulmonary veins, esophagus, and lung as organs susceptible to injuries by DPS [3][4][5][6]. Our case 2 suggested that the diaphragm also requires attention during DPS stitching.…”
Section: Discussionmentioning
confidence: 64%
“…Left lower pulmonary vein flow is depicted using the color Doppler imaging mode. LLPV, left lower pulmonary vein low molecular weight heparin, and the postoperative administration of double antiplatelet agents presumably increased the bleeding [4][5][6]. In contrast, in our two cases, no agents relating to coagulation cascade or platelet function, except a low dose of aspirin or preoperative heparin infusion, were administered.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations